First Responder Virtual Reality Simulator to train and assess emergency personnel for mass casualty response. Issue 1 (16th February 2023) - Kman, Nicholas E.; Price, Alan; Berezina‐Blackburn, Vita; Patterson, Jeremy; Maicher, Kellen; Way, David P.; McGrath, Jillian; Panchal, Ashish R.; Luu, Katherine; Oliszewski, Alex; Swearingen, Scott; Danforth, Douglas
Abstract: As mass casualty incidents continue to escalate in the United States, we must improve frontline responder performance to increase the odds of victim survival. In this article, we describe the First Responder Virtual Reality Simulator, a high‐fidelity, fully immersive, automated, programmable virtual reality (VR) simulation designed to train frontline responders to treat and triage victims of mass casualty incidents. First responder trainees don a wireless VR head‐mounted display linked to a compatible desktop computer. Trainees see and hear autonomous, interactive victims who are programmed to simulate individuals with injuries consistent with an explosion in an underground space. Armed with a virtual medical kit, responders are tasked with triaging and treating the victims on the scene. The VR environment can be made more challenging by increasing the environmental chaos, adding patients, or increasing the acuity of patient injuries. The VR platform tracks and records their performance as they navigate the disaster scene. Output from the system provides feedback to participants on their performance. Eventually, we hope that the First Responder system will serve both as an effective replacement for expensive conventional training methods as well as a safe and efficient platform for research on current triage protocols.